Controlled release of thymol from poly(Lactic acid)-based silver nanocomposite films with antibacterial and antioxidant activity - Ramos, Marina (2020)
Thymol and silver nanoparticles (Ag-NPs) were used to develop poly(lactic acid) (PLA)- based films with antioxidant and antibacterial performance. Different amounts of thymol (6 and 8 wt%) and 1 wt% Ag-NPs were added to PLA to produce the active films. Ag-NPs and thymol were successfully identified in the nanocomposite structures using spectroscopic techniques. A kinetic study was performed to evaluate the release of thymol and Ag-NPs from the nanocomposites to an aqueous food simulant (ethanol 10%, v/v) at 40 °C. The diffusion of thymol from the polymer matrix was affected by the presence of non-migrating Ag-NPs, which showed non-Fickian release behavior. The ternary system including 1 wt% Ag-NPs and 8 wt% thymol showed clear antibacterial performance by reducing the cell viability of Escherichia coli and Staphylococcus aureus by around 40% after 3 and 24 h of storage at 4, 25, and 37 °C compared to neat PLA. Significant antioxidant behavior of all active films was also confirmed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The obtained nanocomposite films based on PLA and the addition of Ag-NPs and thymol were proven to have combined antioxidant and antibacterial performance, with controlled release of thymol. These formulations have potential applications in the development of innovative and customized active packaging systems to increase the shelf-life of food products.